2021
DOI: 10.1038/s41598-021-02817-8
|View full text |Cite
|
Sign up to set email alerts
|

A fungus infected environment does not alter the behaviour of foraging ants

Abstract: Eusocial insects are exposed to a wide range of pathogens while foraging outside their nest. We know that opportunistic scavenging ants are able to assess the sanitary state of food and to discriminate a prey which died from infection by the entomopathogenic fungus Metarhizium brunneum. Here, we investigate whether a contamination of the environment can also influence the behaviour of foragers, both at the individual and collective level. In a Y-maze, Myrmica rubra ants had the choice to forage on two prey pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…Overall, our data suggest that the mobility and spatial location of M.rubra foragers is not altered by the chemical and mechanical cues associated with the fungal spores. This goes along with previous observations where M.rubra ants were not repelled by the presence of fungal conidia over prey or on foraged areas and were as prone to retrieve these items inside the nest (Pereira & Detrain 2020b, Pereira et al 2021. Further studies should investigate to which extent this lack of early spatial distancing correlates (or not) with social behaviour such as allogrooming by M.rubra nestmates.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, our data suggest that the mobility and spatial location of M.rubra foragers is not altered by the chemical and mechanical cues associated with the fungal spores. This goes along with previous observations where M.rubra ants were not repelled by the presence of fungal conidia over prey or on foraged areas and were as prone to retrieve these items inside the nest (Pereira & Detrain 2020b, Pereira et al 2021. Further studies should investigate to which extent this lack of early spatial distancing correlates (or not) with social behaviour such as allogrooming by M.rubra nestmates.…”
Section: Discussionsupporting
confidence: 82%
“…Or these changes may be mediated more indirectly by changing soil properties and chemistry (Wagner et al, 1997) or plant communities (Whitford & Ettershank, 1975). While some ants avoid soil with higher densities of entomopathogenic fungi (Huang et al, 2020), other ant genera have also been shown to not avoid foraging in areas even if entomopathogenic fungi are present in the environment (Pereira et al, 2021). Ultimately, understanding how ants interact with a broader range of microbial partners can expand our understanding of their role in agroecological processes in understudied regions.…”
Section: Discussionmentioning
confidence: 99%
“…Some social insect species, such as the termites Reticulotermes flavipes, M. michaelseni, Zootermopsis augusticollis , and the ants Acromyrmex striatus , and Formica rufa , avoid fungal-infected areas or nestmates (Myles 2002 , Mburu et al 2009 , Liu et al 2019a ). However, other species, such as Myrmica ruba , do not avoid fungal contamination, including M. brunneum found in surrounding areas (Pereira et al 2021 ). In some instances, social insects can detect but react differentially to diseased workers outside versus inside the nest, with health-detectable cues tunable within the social context (e.g.…”
Section: Cross-talk Between Olfaction Behavior and Immunity: Before C...mentioning
confidence: 99%